Synthesis and electrochemical performances of mixed-valence vanadium oxide/ordered mesoporous carbon composites for supercapacitors. Issue 30 (8th March 2016) - Hao, Liang; Wang, Jie; Shen, Laifa; Zhu, Jiajia; Ding, Bing; Zhang, Xiaogang
Abstract : The highly ordered CMK-3 with short-rod like morphology significantly enhance the electrochemical performance of VO x . Abstract : Mixed-valence vanadium oxide (VO x )/ordered mesoporous carbon (CMK-3) composite (VOC) were synthesized through a facile liquid-phase method followed by calcination. The microstructures of the composite were characterized by X-ray diffraction (XRD), nitrogen adsorption and desorption, X-ray photoelectron spectra (XPS), scanning election microscopy (SEM) and transmission election microscopy (TEM). The relevant results showed that vanadium oxide nanoparticles with mixed valence were successfully embedded in mesoporous channels in the conductive matrix and dispersed on the CMK-3 surface to form the interwoven composite. The introduction of the CMK-3 framework not only improves electron transfer but also prevents the structure collapsing during cycling. As expected, the composite exhibits excellent electrochemical properties. It delivered a specific capacitance of 257 F g −1 at 0.5 A g −1 and maintained 77.3% at 8 A g −1 in 5 M LiNO3 . After 5000 cycles, the capacitance only decreased 20%.